Progresses and Prospects of Neuroprotective Agents-Loaded Nanoparticles and Biomimetic Material in Ischemic Stroke - Chen, Junfa; Jin, Jing; Li, Kaiqiang; Shi, Lin; Wen, Xuehua; Fang, Fuquan (Frontiers in Cellular Neuroscience, 2022)
Ischemic stroke remains the leading cause of death and disability, while the main mechanisms of dominant neurological damage in stroke contain excitotoxicity, oxidative stress, and inflammation. The clinical application of many neuroprotective agents is limited mainly due to their inability to cross the blood-brain barrier (BBB), short half-life and low bioavailability. These disadvantages can be better eliminated/reduced by nanoparticle as the carrier of these drugs. This review expounded the currently hot researched nanomedicines from the perspective of the mechanism of ischemic stroke. In addition, this review describes the bionic nanomedicine delivery strategies containing cells, cell membrane vesicles and exosomes that can effectively avoid the risk of clearance by the reticuloendothelial system. The potential challenges and application prospect for clinical translation of these delivery platforms were also discussed.